2020
DOI: 10.1007/s00300-020-02775-3
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niches of benthic crustaceans in the Pechora Sea suggest that the invasive snow crab Chionoecetes opilio could be an important competitor

Abstract: Expanding human activities alongside climate change, the introduction of invasive species and water contamination pose multiple threats to the unique marine ecosystems of the Pechora Sea in the Russian Arctic. Baseline data on biodiversity and responses to environmental change are urgently needed. Benthic decapod crustaceans are globally distributed and play an important role in fisheries, yet their roles in food webs are less understood. In this study, we used an integrated approach combining stomach content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Trophic studies based on stable isotopes in the Barents Sea show that P . pubescens is less enriched in 15 N compared to all other co‐occurring decapod species (Gebruk et al, 2021; Paar et al, 2019; Spiridonov et al, 2020; Zmudczyńska‐Skarbek et al, 2015). The diet of P .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trophic studies based on stable isotopes in the Barents Sea show that P . pubescens is less enriched in 15 N compared to all other co‐occurring decapod species (Gebruk et al, 2021; Paar et al, 2019; Spiridonov et al, 2020; Zmudczyńska‐Skarbek et al, 2015). The diet of P .…”
Section: Discussionmentioning
confidence: 99%
“…), sea stars, and a native king crab species Lithodes maja (Fuhrmann et al, 2017). In the Pechora Sea, spider crabs, Hyas araneus , and hermit crabs, Pagurus pubescens , have some isotopic niche partitioning, while the relatively recently established non‐indigenous snow crabs Chionoecetes opilio strongly overlap them all (Gebruk et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Snow crabs are benthic omnivores, and their diets typically comprise a wide variety of prey types, including macrobenthos, fish and fishery discards, and other crustaceans (Squires and Dawe, 2003). Thus, decapods are largely involved in predator-prey interactions and are known to compete with other species over food and grounds (Boudreau and Worm, 2012;Gebruk et al, 2021). A number of studies showed that predation could shape benthic communities and production processes (Grosholz et al, 2000;de Rivera et al, 2011), and significant shifts in the ecosystem's trophic structure are described due to increased abundance of benthic decapods (Baum and Worm, 2009).…”
Section: Future Perspectivesmentioning
confidence: 99%